2016
DOI: 10.1016/j.chom.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Histones Are Rapidly Loaded onto Unintegrated Retroviral DNAs Soon after Nuclear Entry

Abstract: Summary Chromosomal structure of nuclear DNA is usually maintained by insertion of nucleosomes into preexisting chromatin, both on newly synthesized DNA at replication forks and at sites of DNA damage. But during retrovirus infection, a histone-free DNA copy of the viral genome is synthesized that must be loaded with nucleosomes de novo. Here we show that core histones are rapidly loaded onto unintegrated Moloney murine leukemia virus DNAs. Loading of nucleosomes requires nuclear entry but does not require vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 67 publications
4
48
0
Order By: Relevance
“…Our data, and previous work from the Goff laboratory, are consistent with the hypothesis that proviral DNA integration allows escape from the epigenetic silencing that occurs if integration is blocked (17). However, this hypothesis does not preclude the possibility that integration also facilitates other aspects of retroviral replication.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data, and previous work from the Goff laboratory, are consistent with the hypothesis that proviral DNA integration allows escape from the epigenetic silencing that occurs if integration is blocked (17). However, this hypothesis does not preclude the possibility that integration also facilitates other aspects of retroviral replication.…”
Section: Discussionsupporting
confidence: 90%
“…These increases in viral DNA and protein expression were lost when a replication incompetent, env-deficient HIV-1 was analyzed, and hence must result from virus spread ( Fig. 2E and F Previously, it has been reported that unintegrated retroviral DNA is rapidly chromatinized after nuclear entry and then decorated with inhibitory epigenetic marks that are removed, by an unknown process, after integration occurs (16,17). Here, we demonstrate that Tax expression also reduces the deposition of inhibitory chromatin marks, and increases the deposition of activating marks, on unintegrated proviral DNA (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Like several other DNA viruses and retroviruses (e.g., herpes simplex virus, Kaposi's sarcoma-associated herpesvirus, simian virus 40, and murine leukemia virus), the HAdV DNA associates with cellular histones during specific stages of the virus life cycle (60)(61)(62). Modifications of these histones has very recently been shown to modulate HAdV gene expression (34), but many questions regarding the "chromatinization" and epigenetic regulation of the HAdV genome still remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly resembles freshly synthesized (linear) retroviral DNA that can either integrate (as desired by the virus) or be “repaired” to dead-end single long terminal repeat (LTR) circles via intramolecular homologous recombination of the two LTRs, and double LTR circles by non-homologous end-joining (NHEJ) [47,135]. …”
Section: Evidence For a Connection Between Hbv And The Host Dna Damentioning
confidence: 99%